Potential and strategies for implementing constructed wetland technology to mitigate water pollution in Ha Noi’s lakes and ponds, Viet Nam - Anh, Bui Thi Kim; Thanh, Nguyen Van; Kim, Dang Dinh; Ngoc, Dao Quang; Ha, Nguyen Thi Hoang; Phuong, Nguyen Minh; Thuy, Pham Thi (Vietnam Journal of Science and Technology, 2025)
Constructed wetland (CW) technology emerges as a highly effective, sustainable, and eco-friendly solution for tackling water pollution. This report provides an overview of CW technology and its potential application in treating water pollution in Hanoi's lakes and ponds in Vietnam. Based on existing research, the report synthesizes CW systems' definition, classification, and treatment efficiency while proposing appropriate implementation strategies for Hanoi’s lakes. Low-pollution lakes should utilize cost-effective free-floating plants, whereas highly polluted lakes require subsurface flow or hybrid CW systems to achieve high treatment efficiency. The implementation roadmap consists of three phases: assessing the current status, piloting the model, and scaling up the application alongside source control measures and operational monitoring. Although CWs technology are a sustainable and viable solution, their widespread adoption in managing water quality in Hanoi's lakes and ponds requires thorough evaluation, careful selection of suitable technologies, and integration with comprehensive and long-term policies.